Yearbook of the United Nations 1997 - United Nations (United Nations, 1997)
The 1997 edition of the Yearbook of the United Nations details the many activities of the Organization and its organs, programmes and bodies, as they are carried out in all corners of the globe. It gives an account of their endeavours to create better and more peaceful conditions for all mankind and record their efforts to deal with matters of pressing concern in a variety of areas, including peacekeeping and peacemaking, disarmament, human rights, trade and development, control of drug abuse and illicit trafficking, crime prevention, assistance to refugees and other vulnerable populations. This 1,652 pages volume is fully indexed and reproduces all major General Assembly, Security Council and Economic and Social Council resolutions issued during the year.